PEMODELAN DAN SIMULASI SKEMA PELEPASAN BEBAN DENGAN RELE FREKUENSI RENDAH SISTEM KELISTRIKAN DI PT. PLN (PERSERO) KOTA KENDARI - Sartisya, Risya; Hay, Sahabuddin; Siti Nur Alam, Wa Ode (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2020)
The deviation of the frequency of a power system from its nominal value is a reflection of the mismatch between generation and load. Such deviation are serious and must be monitored and controlled very closely. One major impact of operation outside a narrow range around the nominal frequency is that generators can demaged. To avoid this, manufacturers set time interval limits for under-frequency operation and when such limits are exceeded, the generator trips. Howeever, unless generator tripping is coordinated with some accompanying load shedding, the system inablitiy to supply its load can be exacerbated resulting in an even worse frequency deviation.Under-frequency load shedding (UFLS) is designed to protect the power system from event leading to a sudden drop in system frequency, when the primary frequency regulation built into the generation system is not enough to bring the frequency back to nominal. Under-frequency load shedding disconnect blocks of load when the frequency drop below given threshold. This study aims to model and simulate each stage of the shed of the load that is in the electrical system of the city of Kendari using low frequency relays and assess the effectiveness of each stage to return the system frequency and voltage to the value that is still permitted.The results showed that the simulation of each stage of load release with the help of DigSilent Power Factory 10.1.7 software was able to minimize the amount of outages, and was able to restore the System frequency when the frequency was minimal due to the sudden loss of power suppliers(generator). The frequency recovery rate of the study shows the release of loads starting from 2.57 MW - 3.33 MW frequency recovery from 49.4 Hz - 50.00 Hz.Keywords: Frequency and Voltage, Loss generator, Under-Frequency Load Shedding.